Ornithological and molecular evidence of a reproducing Hyalomma rufipes population under continental climate in Europe - Keve, Gergő; Csörgő, Tibor; Benke, Anikó; Huber, Attila; Mórocz, Attila; Németh, Ákos; Kalocsa, Béla; Tamás, Enikő Anna; Gyurácz, József; Kiss, Orsolya; Kováts, Dávid; Sándor, Attila D.; et al. (Frontiers in Veterinary Science, 2023)
Reports on adult Hyalomma ticks in certain regions of the Carpathian Basin date back to the 19th century. These ticks were thought to emerge from nymphs dropping from birds, then molting to adults. Although the role of migratory birds in carrying ticks of this genus is known from all parts of Europe, in most countries no contemporaneous multiregional surveillance of bird-associated ticks was reported which could allow the recognition of hotspots in this context. From 38 passeriform bird species 956 ixodid ticks were collected. Tick species were identified as Ixodes ricinus (n=598), Ixodes frontalis (n=18), Ixodes lividus (n=6), Haemaphysalis concinna (n=321), and D. reticulatus (n=1). All 12 Hyalomma sp. ticks (11 engorged nymphs and 1 unengorged larva) were identified as H. rufipes based on three mitochondrial markers. This species was only found in the Transdanubian region and along its southeastern border. The Common Blackbird and the European Robin were the two main hosts of I. ricinus and I. frontalis, whereas H. concinna was almost exclusively collected form long-distance migrants. The predominant hosts of H. rufipes were reed-associated bird species, the Sedge Warbler and the Bearded Reedling, both in their nesting period. This study provides ornithological explanation for the regional, century-long presence of adult Hyalomma ticks under continental climate in the Transdanubian Region of the Carpathian Basin. More importantly, the autochthonous occurrence of a H. rufipes population was revealed for the first time in Europe, based on the following observations: (1) the bird species infested with H. rufipes are not known to migrate during their nesting period; (2) one larva was not yet engorged; (3) the larva and the nymphs must have belonged to different local generations; and (4) all H. rufipes found in the relevant location were identical in their haplotypes based on three maternally inherited mitochondrial markers, probably reflecting founder effect. This study also demonstrated regional and temporal differences in tick species carried by birds.